A Single-center, Single Blinded, Randomized Controlled Trial Protocol of Therapeutic Listening Programme Versus Traditional Music Therapy on Depression and Quality of Life in Institutionalized Adolescents (Medico Legal Update, 2021)
Introduction: Depression is a typical, constant, and debilitating issue occurring during adolescence andinfluencing near a fourth of all grown-ups. In adolescents, depression related with impaired social connections,lower educational accomplishment, poor scholarly execution, family and social brokenness, physical sickwellbeing and expanded danger of self-destruction. Music therapy intervention could essentially diminishedsymptoms of depression, increased cognitive functioning and improved quality of lifeObjective: To determine the effects of therapeutic listening programme versus traditional music therapy onDepression and Quality of Life in Institutionalized Adolescents.Method: A single-center, single blinded, two group pretest-posttest randomized controlled trial of 36institutionalized adolescents with depression will be recruited through the simple random sampling. Recruitedinstitutionalized adolescents will be randomized into one of the two groups namely, therapeutic listeningprogramme group and traditional music therapy group through block randomization. Both the groups willreceive their respective interventions for 30 minutes a day, 2 days a week for 8 weeks. Participants in dancegroup performed, 30 minutes of dance for 3 days/week for 6 weeks. The primary outcome measures willbe Children’s Depression Inventory (CDI) and Youth Quality of Life Instrument – Short Form (YQOL-SF).Urine test and electroencephalogram (EEG) will be recorded in addition to CDI and YQOL-SF. All theoutcome measures will be measured at baseline and 8 weeks post intervention.Results: Normality of the collected data will be analyzed using Shapiro-Wilk test of normality. Descriptivestatistics will be expressed in mean±Standard deviation/mean (95% confidence interval) with range andparametric tests/non-parametric tests, paired t-test/Wilcoxon signed rank test and independent t-test/MannWhitney U-test will be used for within and between group comparisons based on normality.Conclusion: The study outlines the importance of therapeutic listening programme on institutionalizedadolescents with depression. Successful completion of this RCT will create evidence on the best treatmentoptions for institutionalized adolescents with depression